On the Application of Oxynitride Thin Films in Biomedicine; Journal of Surface Investigation: X-ray, Synchrotron and Neutron Techniques; Vol. 18, iss. 1 supplement - Filimonova V. S. Valeriya Sergeevna; Karelin S. Yu, Stanislav Yurjevich; Krasnobaeva L. A. Larisa Aleksandrovna; Gusakova S. V. Svetlana Valerjevna; Lisichko E. V. Elena Vladimirovna; Nikitenkov N. N. Nikolai Nikolaevich; Sypchenko V. S. Vladimir Sergeevich (2024, 2024)
Title screen